ANALYSIS OF THE IMPLEMENTATION OF THE BOK POLICY IN INCREASING BASIC IMMUNIZATION COVERAGE AT THE BLANGKEJEREN CITY CARE CENTER, GAYO LUES REGENCY, ACEH PROVINCE - Lubis, Masrida Riviah; Anggraini, Indah; Nasution, Ramadhani Syafitri (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Complete basic immunization coverage is an important indicator in improving public health status. The government through the Health Operational Assistance (BOK) policy seeks to strengthen access and quality of immunization services, but in some areas coverage is still low. This study aims to analyze the implementation of BOK policies in increasing basic immunization coverage at the Blangkejeren City Treatment Health Center, Gayo Lues Regency, Aceh Province. The research method used a qualitative approach with in-depth interviews. The main informants are the head of the health center, the core informant in charge of the BOK program, and the supporting informant of the three midwives implementing immunization. Triangulation was carried out with five mothers under five. Data analysis uses thematic analysis techniques. The results of the study show that the implementation of BOK supports the implementation of basic immunization, but is not optimal. Supporting factors include routine fund allocation, coordination, and a positive attitude of officers. The main obstacles are limited health workers, ineffective planning and reporting, and low public participation due to lack of information and myths about vaccine side effects. In conclusion, BOK policies have helped the implementation of basic immunization, but there is still a need to strengthen coordination, program planning, and public education so that immunization coverage can be increased overall.